MENINGKATKAN KEMAMPUAN KONEKSI MATEMATIS SISWA SMP KELAS VII MENGGUNAKAN PENDEKATAN PEMBELAJARAN BERBASIS MASALAH PADA MATERI SEGITIGA DAN SEGIEMPAT - Muhamad Rizki Hidayat; M Jalaludin; Euis Eti Rohaeti; M Afrilianto (IKIP Siliwangi, 2018)
This study aims to examine and analyze about problem-based learning approach to improve connection ability in SMP. The population in this research is VII SMP in Karawang. This study was designed qualitative descriptive method. Based on the results and discussion students connection ability had improved. It is known from the number of students who experience improvement in each cycle. In the first cycle shows that the results of mathematics learning on triangle and quadriplegic classically obtained scores of students from the questions given in the first cycle test, obtained 18 students reached 60% of 30 students who are able to obtain value above the KKM while in cycle II shows that the results of mathematics learning on triangle and quadrilateral material has reached 83.34% or as many as 25 students from 30 junior high school students who get grade VII above the KKM with an average value of 83. This shows an increase of 23.34% as many as 7 people students from the first cycle test. Means only 9% or as many as 5 students still score below the KKM.